Utilization of Pregnant Mare Serum Gonadotrophin (PMSG) for Superovulation in Earthworm (Lumbricus rubellus) Cocoon Production - Merta, I Wayan; Kusmiyati, Kusmiyati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Earthworms (Lumbricus rubellus) belong to the phylum Annelida, class Clitellata, order Haplotaxida, family Lumbricidae, and genus Lumbricus. They thrive in loose and moist soil habitats. This species is commonly used as animal feed due to its high protein content, which is 65% higher than that of mammalian meat and 50% more than that of fish. To meet the increasing demand for earthworms as livestock and fish feed, their cultivation and production need to be enhanced. One method to boost earthworm production is by manipulating their reproduction through superovulation using Pregnant Mare Serum Gonadotrophin (PMSG). PMSG is a hormone produced by the chorionic cups of pregnant mares and has biological effects similar to Follicle-Stimulating Hormone (FSH) and minor Luteinizing Hormone (LH) activity. This study used a completely randomized design consisting of four groups: the control group (K0) without PMSG treatment, treatment group 1 (K1) receiving 200 IU PMSG dissolved in 100 ml of distilled water, treatment group 2 (K2) receiving 250 IU PMSG dissolved in 100 ml of distilled water, and treatment group 3 (K3) receiving 300 IU PMSG dissolved in 100 ml of distilled water. The treatment was applied by immersing the earthworms in the solution for 2 minutes. Each treatment group contained 10 earthworms and was replicated 10 times. Data were analyzed using one-way ANOVA at a 5% significance level, followed by the Least Significant Difference (LSD) test. The results of this study indicate that the administration of Pregnant Mare Serum Gonadotrophin for superovulation significantly increases cocoon production in Lumbricus rubellus.